A national survey of academic articles reading and retrieving of laboratory professionals - Chen, Ying; Wang, Zhenzhen; Li, Ying; Gu, Bing; Li, Hongchun (Journal of Laboratory and Precision Medicine, 2017)
Background: The laboratory medicine is usually an important hub between the patient and health care system in aspects of diagnosis and monitory of diseases. With so much attention drawn toward the provision of quality laboratory services, it becomes imperative to assess the knowledge of laboratory professionals. This work was therefore aimed at understanding the learning and working situation of laboratory professionals through the investigation of article reading and retrieving. Methods: The questionnaire designed by “Questionnaire Star” was launched for a month. The survey was conducted among the national laboratory professionals by WeChat from September 27, 2016 to October 27, 2016. The outcome was retrieved and analyzed by “Questionnaire Star” again. Results: There are 883 questionnaire replies across more than 30 districts in the survey. The responders are the laboratory professionals from different positions including the university students, the postgraduate students, the staffs working at hospital, teachers, retired staffs and so on. When talking about the frequency of literature reading, 59.3% of them chose “monthly or yearly”, 25.8% of them chose “weekly”, 9.1% of the repliers preferred to “daily” and 5.9% never do it. As regards the frequency of consulting academic databases, 37.9% of responders accessed scientific databases weekly and 33.2% accessed monthly, followed were yearly (14.2%), daily (8.1%) and never (6.1%). In addition, we found that 55.4% of the responders never published articles and 40.3% whose article publication numbers were less than 5 every year. Of course, the impact factors of those publications were less than 5 (89.1%) mostly. Conclusions: The articles reading and retrieving situation of laboratory professionals were simply found by this survey. And it will have a positive influence on the improvement of their specialty learning.